Construction of EMSC-Islet Co-Localizing Composites for Xenogeneic Porcine Islet Transplantation. (July 2018) - Kim, Jung-Sik; Shin, Jun-Seop; Kim, Sang-Joon; Park, Chung-Gyu
Abstract : Background: Pancreatic islet transplantation is an ultimate solution for treating patients with type 1 diabetes. The pig is an ideal donor of islets for replacing scarce human islets. Besides immunological hurdles, non-immunological factors including fragmentation and delayed engraftment of porcine islets need to be solved for successful porcine islet xenotransplantation. In this study, we suggest a simple but effective modality, a cell/islet co-localizing composite, to overcome these challenges. Methods: Murine mesenchymal stem cells (MSCs) were prepared from bone marrow, and endothelial-like mesenchymal stem cells (EMSCs) were differentiated from MSCs with optimized culture conditions. Differing amounts of MSCs and EMCs were co-cultured with isolated porcine islet cells (1000 IEQs) to generate MSC- and EMSC-islet co-localizing composites. The composites were assessed for their magnitude of fragmentation, mass preservation, and in vitro angiogenesis potential. Results: MSCs and EMCs evenly coated the surface of porcine islets (>85%) through optimized culture conditions. Both MSCs and EMSCs significantly reduced the fragmentation of porcine islets and increased the islet masses, designated as IEQs. In fibrin in vitro angiogenesis analysis, constructed EMSC-islet composites showed higher angiogenic potentials than naked islets, human endothelial cell-islet composites, and MSC-islet composites. Conclusions: This novel delivery method of EMSC-porcine islet co-localizing composites may have beneficial effects on the engraftment of transplanted islets by prevention of fragmentation and enhancement of revascularization. This work was supported by a grant from the Korea Healthcare Technology R&D Project through the Korea Health Industry Development Institute (KHIDI), funded by the Ministry for Health and Welfare, Republic of Korea (Grant No. HI13C0954). Figure. No caption available.